The Participation of Women in the Armed Resistance in 1944–1953 - Smolskutė, Žaneta (Genocidas ir rezistencija, 2006)
This article deals with the motives behind the participation of women activists in the resistance from 1944 to 1953, their status in the partisan war, and the main features and characteristics of their activities. After archive documents about 250 active women fighters had been systematised, a preliminary chart of the changes in the participation of women in the armed resistance between 1944 and 1953 was drawn up. An analysis of statistical research made it possible to assume that in different years of the partisan war, the active participation of women in the armed resistance was different, as well as to discern some regularities in the general context of the resistance. The year 1945 is considered in historiography the most active. Statistical research shows that the largest number of women joined partisan units in that year. The conclusion can be drawn that the active involvement of both women and men in the ranks of the fighters was conditioned by the general tendencies in the resistance to the occupation. At the beginning of the partisan movement, during the general ideological upsurge, there were no strict regulations concerning women joining the ranks of the partisans. The war was still going on in Europe, and nobody expected the occupation to last long. There were not many women who had the status of partisan; most girls belonged to the category of messengers and supporters. A statistical study shoes that married women accounted for 72 percent of the active fighters, while single girls made up 28 percent. As the wives of the partisans were badly affected most of them joined partisan units. From 1946 the number of active fighters started falling. The political situation, the tactics of the resistance and the conditions for the partisans had changed. From 1948 more women than men were arrested. This can be linked to the deportations in 1948 and 1949. All of this could have influenced the suddenly reduced numbers of women fighters from 1949. That year, the Lithuanian Freedom Fighters Movement decided to stop accepting women into the ranks of active fighters, which could have been an important factor. Therefore, unit leaders provided women with false documents and sent them out of the forests. When there were no chances of finding refuge with trusted people, women hid with partisans. When the partisans were betrayed, or the Cheka succeeded in locating them, some women were killed in the forests, while others blew themselves up in bunkers. As a result of this, from 1949, more women were killed. During the last stage of the resistance, there were fewer women fighters than at the beginning of the movement, but due to the changed conditions for the partisans, more of them were killed. It is evident from the documents of the Lithuanian Freedom Fighters Movement that women partisans were treated in the same way as men. They participated in military operations and carried out leaders’ orders. Just like the men’s, when killed their dead bodies were displayed on town squares. Although women did not hold high positions, they had responsible roles as messengers, paramedics and defence heads at headquarters. Not all women who joined the underground had weapons, and not all were active fighters. Some of them did daily chores, such as cooking and laundry. In order to play down their role in the resistance, women often gave false evidence when they were interrogated by the Soviets: being afraid of the partisans, they did what they were told. However, the partisan initiative to urge girls to join the resistance had a real basis. Sometimes men had to dress as women, which shows how specific women’s work in the resistance was. That partly explains the partisans’ efforts to enlist women’s help to work as scouts and messengers.